Resource papers as registered reports: a proposal - Emiel van Miltenburg (Northern European Journal of Language Technology)
This is a proposal for publishing resource papers as registered reports in the Northern European Journal of Language Technology. The idea is that authors write a data collection plan with a full data statement, to the extent that it can be written before data collection starts. Once the proposal is approved, publication of the final resource paper is guaranteed, as long as the data collection plan is followed (modulo reasonable changes due to unforeseen circumstances). This proposal changes the reviewing process from an antagonistic to a collaborative enterprise, and hopefully encourages NLP resources to develop and publish more high-quality datasets. The key advantage of this proposal is that it helps to promote responsible resource development (through constructive peer review) and to avoid research waste.